Production of protein-enriched bread through the incorporation of the black soldier fly (Hermetia illucens) larvae - Siqueira Galvão Novo, Gabriel; César Tondo, Eduardo; Cruz Silveira Thys, Roberta; Cladera, Florencia (Food Science and Technology, 2024)
The aim of this study was to produce protein-enriched bread using the black soldier fly larvae (Hermetia illucens) powder with the addition of ascorbic acid and mono- and diglycerides. In total, 11 bread formulations were produced using fixed amounts of wheat flour (100%), salt (2%), yeast (3%), black soldier fly larvae powder (15%), and variable amounts of mono- and diglycerides (0–0.8%), ascorbic acid (0–200 ppm), and water (50–70%), according to a 2³ factorial design. Black soldier fly larvae powder showed high protein (42%, dry weight) and lipid levels (29%, d.w.). Enriched breads were darker and exhibited enhanced nutritional quality, with a 48% increase in the protein content, a 21 times increase in the lipid content, and a 1.5 times increase in the ash content. Samples with 60% and 70% water had comparable or better values for the parameters analyzed (baking loss, specific volume, crumb structure, and hardness) when compared with a control bread. The incorporation of 15% of black soldier fly larvae powder in wheat breads improved its nutritional quality while maintaining acceptable technological parameters when used in combination with the mono- and diglycerides and the ascorbic acid. The aim of this study was to produce protein-enriched bread using the black soldier fly larvae (Hermetia illucens) powder with the addition of ascorbic acid and mono- and diglycerides. In total, 11 bread formulations were produced using fixed amounts of wheat flour (100%), salt (2%), yeast (3%), black soldier fly larvae powder (15%), and variable amounts of mono- and diglycerides (0–0.8%), ascorbic acid (0–200 ppm), and water (50–70%), according to a 2³ factorial design. Black soldier fly larvae powder showed high protein (42%, dry weight) and lipid levels (29%, d.w.). Enriched breads were darker and exhibited enhanced nutritional quality, with a 48% increase in the protein content, a 21 times increase in the lipid content, and a 1.5 times increase in the ash content. Samples with 60% and 70% water had comparable or better values for the parameters analyzed (baking loss, specific volume, crumb structure, and hardness) when compared with a control bread. The incorporation of 15% of black soldier fly larvae powder in wheat breads improved its nutritional quality while maintaining acceptable technological parameters when used in combination with the mono- and diglycerides and the ascorbic acid.